With the guerrilla in power there should be no excuse for peace - Rosero, Robert Posada (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The political moment that the country demands requires opening a deep, honest and balanced dialogue on the causes of the conflict in Colombia and the historical obstacles that were posed as immovable in the search for national reconciliation that leads to the long-awaited total peace. With the idea of ​​advancing in this exercise of comprehensive analysis, I ventured to read the books 'Hidden Chronicle of the Conflict' by the writer, actor and theater director Manuel Giraldo, a look at our tragic reality from the perspective of a leftist militant, and Behind the war in Colombia, by the deputy academic director of the Peace and Reconciliation Foundation and now senator for the Green Alliance party, Ariel Ávila, a necessary approach to try to find that intermediate point that transcends the extremes.